2010
DOI: 10.1136/gut.2009.200873
|View full text |Cite
|
Sign up to set email alerts
|

Influence of seasonal variations in ambient temperatures on performance of immunochemical faecal occult blood test for colorectal cancer screening: observational study from the Florence district

Abstract: This study showed that there is a significant fall in Hb concentration at higher ambient temperatures. These results will have important implications for the organisation of immunochemical FOBT-based screening programmes, particularly in countries with high ambient temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 22 publications
8
90
2
2
Order By: Relevance
“…Again the greater participation was found with FIT (59.6% vs. 46.9%, P , 0.001). Because of the hot climate in Israel, and our previous experience of the degradation of FIT by heat, 27,28 participants in the FIT arm were requested to keep the samples in their refrigerator at home and bring the samples back using cooling bags. Our design was, therefore, much more demanding for the FIT arm (three samples, keeping the samples in the refrigerator), although in the gFOBT arm there were dietary restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…Again the greater participation was found with FIT (59.6% vs. 46.9%, P , 0.001). Because of the hot climate in Israel, and our previous experience of the degradation of FIT by heat, 27,28 participants in the FIT arm were requested to keep the samples in their refrigerator at home and bring the samples back using cooling bags. Our design was, therefore, much more demanding for the FIT arm (three samples, keeping the samples in the refrigerator), although in the gFOBT arm there were dietary restrictions.…”
Section: Discussionmentioning
confidence: 99%
“…15 Given the study design, we can exclude seasonal variations in positivity rates. 16 On the other hand, we can argue that the accompanying letter, with very short written instructions and sent only to participants in the mailing arms, may have positively influenced their behavior in returning samples.…”
Section: Impact On Participationmentioning
confidence: 99%
“…Nevertheless, several studies have shown the good performance of Magstream in population surveys, even using only 1 sample at the manufacturer's threshold (17,18). Costs of the tests should also be considered, together with adaptation of screening programs to limit the effect of sensitivity of tests to temperature on their performances (12). Further studies and cost-effectiveness analysis are needed to compare Magstream and OC-Sensor in real screening settings, appropriately taking into account temperature and duration of storage.…”
Section: Discussionmentioning
confidence: 99%
“…At 30 C, the performance of Magstream and FOB Gold was very poor, whereas the OC-Sensor was much better and remained reliable, even at this high temperature. I-FOBT sensitivity variations related to storage duration have previously been described in both laboratory experiments and genuine screening settings (11)(12)(13)(14). The interaction between storage duration and temperature has been quantified for the OC-Sensor test in a laboratory experiment: The daily decrease in fecal Hb measurement was 0.3% at 4 C, 2.2% at 20 C, and 3.7% at 28 C (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation